(untitled) (Experimental biology, 2023)
The article discusses the effect of the plant immunomodulator 1(10)β-epoxy-5,7α,6β(Н)-guai-3(4),11(13)-diene-6,12-olide (hereinafter referred to as epoxyguaianolide) on the immune system of the cancer patients. According to the results of randomized clinical trials, the immunomodulatory effect of epoxyguaianolide was confirmed and its positive effect on the indicators of the LPO-AOD system and oxidative modification of proteins was determined. The paper shows the importance of immunophenotypic analysis of peripheral blood mononuclear cells of cancer patients. The immunomodulatory effect of epoxyguaianolide was determined, which manifests itself as a predominant effect on the T-cell link of immunity. Epoxyguaianolide has the ability to correct the immunosuppressive effect of cytostatics. Thus, the results of studies of epoxyguaianolide indicate the potential for the development of a new drug based on it with a pronounced cytostatic effect, thereby stimulating the immune system.